Binocular vision measurement and its application in full-field convex deformation of concrete-filled steel tubular columns. (December 2018) - Tang, Yun-Chao; Li, Li-Juan; Feng, Wen-Xian; Liu, Feng; Zou, Xiang-Jun; Chen, Min-You
Highlights: The binocular vision-based measurement method is proposed. The vision system containing image acquisition, processing and calculation is constructed. The non-contact method results truly reflect the deformation process and full-field strain values. Relative error of binocular vision method is 0.19% for displacement and 0.20% for strain. The proposed method can be used as a reasonable alternative to traditional contact method. Abstract: This paper presents a non-contact 3D deformation measurement method based on binocular vision. The proposed method was tested in the determination of the deformation and strain of concrete-filled steel tubes. Based on the proposed image-processing algorithm and the principle of 3D deformation measurement, the least-square-based circle-fitting algorithm was presented in this article and was applied to binocular vision systems for the static and dynamic collection of full-field 3D deformation data in concrete-filled steel tubular columns. Three-dimensional reconstruction was performed, and the results obtained were compared with those of a contact measuring tool. The test results showed that the mean relative errors of the maximum convex diameter in the visual static and dynamic measurements were 0.19% and 0.33%, respectively, and the mean relative error in the full-field strain in the visual measurement was between 0.20% and 0.49%, which shows that the proposed visual method comprehensively reflects the deformation process and full-field strain values of the components under engineering ISO Tolerance (IT7) accuracy requirements. This method can be used as a reasonable alternative to traditional contact measuring methods.